INFLUÊNCIA DE ELEMENTOS EXTERNOS NOS FATORES QUE GERAM O SURGIMENTO E CRESCIMENTO DO MOFO - Silveira, Vinicius de Castro; Westphal, Fernando Simon (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The emergence of isolated building systems, which increasingly seek to reduce heat exchanges between the exterior and interior of buildings, directly affect the user, which reduces the number of times the window opens, reducing the amount of air per hour. With this reduction of air, the appearance of dew points becomes more frequent, and joining these factors to an unfavorable solar orientation, the appearance of mold on the inner surfaces of the walls becomes practically unavoidable. In order to understand the real influence of the use of insulation or not, solar orientation and air changes per hour in the parameters that can be propellants for the appearance of the mold, simulations and a crossanalysis of data will be carried out, in order to understand the real one influence of each parameter on mold growth and appearance. Data collection will be performed through simulations in EnergyPlus, reproducing the characteristics of the materials realistically in a typical year for the city of Florianopolis